Analysis of isolated transverse process fractures sustained during blast-related events. Issue 1 (July 2018) - Newell, Nicolas; Pearce, A. Phillip; Spurrier, Edward; Gibb, Iain; Webster, Claire E.; Clasper, Jonathan C.; Masouros, Spyros D.
Abstract : BACKGROUND: Personnel have sustained a range of devastating blast injuries during recent conflicts. Previous studies have focused on severe injuries, including to the spine; however, no study has specifically focused on the most common spinal injury—transverse process (TP) fractures. Although their treatment usually requires limited intervention, analysis of TP fractures may help determine injury mechanisms. METHODS: Data were collected from victims with spinal fractures who were injured in improvised explosive device attacks, from the UK's Joint Theatre Trauma Registry. The level and side of each TP fracture were recorded, as well as associated injuries, whether they were mounted or dismounted, and outcome (survivor or fatality). RESULTS: Most (80%) of the TP fractures were lumbar. More bilateral (both left and right fractures at the same level), and L5 TP fractures, were seen in fatalities than survivors. In the mounted group, lumbar TP fractures were statistically significantly associated with fatality, head injury, noncompressible torso hemorrhage, pelvic injury, and other spinal injuries. In the dismounted group, thoracic TP fractures were associated with head, chest wall, and other spinal injuries; and lumbar TP fractures were associated with pelvic and other spinal injuries. CONCLUSIONS: Different injury mechanisms of the TP in the mounted and dismounted groups are likely. Inertial forces acting within the torso due to rapid loading being transferred through the seat, or high intra-abdominal pressures causing the tensile forces acting through the lumbar fascia to avulse the TPs are likely mechanisms in the mounted group. Blunt trauma, violent lateral flexion-extension forces, or rapid flail of the lower extremities causing tension of the psoas muscle, avulsing the TP, are likely causes in the dismounted group. Isolated lumbar TP fractures can be used as markers for more severe injuries, and fatality, in mounted blast casualties. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III.